Los gobiernos descentralizados y las hidroeléctricas :caso proyecto hidroeléctrico La Victoria, parroquia Cuyuja, cantón Quijos, provincia de Napo, año 2012-2014. - Goyes Vallejo, Lady Elizabeth (2016)
The systematization attempts to reflect the mechanisms of negotiation, coordination and control, as well as major critical nodes and the different perceptions that generate about as complex as the presence of hydropower in a given territory subject. The case of Hidroelectrica La Victoria in the parish Cuyuja province of Napo, moves between the expectation of improvement in the living conditions of its inhabitants and disenchantment regarding compliance with commitments and plans. The axis of the paper focuses on the processes of coordination and participation of the various stakeholders The relationship between Hidroelectrica La Victoria and autonomous governments Quijos Municipal and Parish Cuyuja , begins with disagreements since it does not occur in a framework of coordination and recognition of local authorities; in the course of the implementation and execution of the project, the level of coordination improvement and possible to establish consensus , allowing municipalities to establish agreements under the Strategic Plans for the implementation of compensatory and emerging results works that fail to meet the expectations of the population regarding the implementation schedule of works , as in any process, there is more than one reading or look the other side of the experience highlights the generation of jobs , improving the income of the population, boosting trade and other activities that are conducive to the welfare of the community.